Finding The Best Feeding Point Location Of Patch Antenna Using HFSS - Jasim, S. E.; Mohamad Ashry, Jusoh; Muhammad Hafiz, Mazwir; S. N. S., Mahmud (Asian Research Publishing Network (ARPN), 2015)
This paper describes about the finding of an optimal location of feeding location for patch antenna by using Ansoft HFSS software. The dimensions of patch antenna were calculated based on the three essential parameters. The operation frequency of patch antenna was designed at 2.4 GHz. The LaAlO3 was chosen as a substrate material for the designed patch antenna with a dielectric constant of 23.5, and a height of 1.5 mm. The materials were chosen as a perfect conductor for patch and ground plane with a cut off area from a substrate block. The centre of the patch as well as substrate is located at the origin coordinates of x-y plane, and the height of substrate at z-direction. The objective of this paper is to find the best feed point location, which achieves the highest performance for the designed antenna. The best feed point is located at (Xm, Yn) from the origin. The simulation was done for all feed point locations. The return loss was calculated, and it has the highest value of return loss at a constant y-axis point along the length of patch antenna. The results demonstrated that the use of such a design will achieve high directivity, gain, efficiency, and performance.